2023
DOI: 10.1101/2023.04.07.23288301
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomics reveals novel microbial signatures of farm exposures in house dust

Abstract: Indoor home dust microbial communities, important contributors to human health outcomes, are shaped by environmental factors, including farm-related exposures. Detection and characterization of microbiota are influenced by sequencing methodology; however, it is unknown if advanced metagenomic whole genome shotgun sequencing (WGS) can detect novel associations between environmental exposures and the indoor built-environment dust microbiome, compared to conventional 16S rRNA amplicon sequencing (16S). This study… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…(24) (ALHS data release P3REL201209.00) Further details on the study design and inclusion criteria can be found elsewhere. (18,19) Of the full ALHS cohort (N=3301), 2871 participants completed a home visit between 2009 to 2013 with vacuumed bedroom dust collection. (25) The Institutional Review Board at the National Institute of Environmental Health Sciences approved the study.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 4 more Smart Citations
“…(24) (ALHS data release P3REL201209.00) Further details on the study design and inclusion criteria can be found elsewhere. (18,19) Of the full ALHS cohort (N=3301), 2871 participants completed a home visit between 2009 to 2013 with vacuumed bedroom dust collection. (25) The Institutional Review Board at the National Institute of Environmental Health Sciences approved the study.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…A subset of 879 dust samples were sent for microbiome analysis, with sample selection described elsewhere. (18,19,25) DNA extraction followed standard protocols following manufactured kits and is described elsewhere. (18,19) Extracted DNA samples were sent to the University of California San Diego IGM Genomics Center for library preparation, multiplexing, and whole genome shotgun sequencing using standard techniques.…”
Section: Home Dust Microbiome Examinationmentioning
confidence: 99%
See 3 more Smart Citations